협력과 대립 : 근대 중국 서의계(西醫界)의 파벌문제 - 조정은(JO Jeongeun) (Daehan yisa haghoeji, 2016)
After the defeat of the Opium War and the Sino-Japanese War, China’s intellectuals realized necessity of modernization (Westernization) to survive in the imperial order of the survival of the fittest. In particular, it was urgent to accept Western medicine and train the doctors who learned Western medicine to change the sick and weary Chinese to be robust. Thus, new occupations of the Western Medicine Group (xiyi, doctors who learned Western medicine) emerged in China. As with the first profession, the new Western Medicine Group tried to define standards of Western medicine and medical profession; however, it was difficult in the absence of the strong central government. In addition, they formed a faction by the country where they studied or the language they learned. The factions included the Britain - America faction(yingmeipai) consisting of the Britain - America studied doctors or graduates from Protestant missions based medical schools, and the Germany - Japan faction(deripai), graduates from medical schools by Japanese or German government and the Chinese government. In 1915, they founded the National Medical Association of China mainly consisting of the Britain - America faction and the National Medical and Pharmaceutical Association of China led by the Germany – Japan faction. Initially, exchanges were active so most of eminent doctors belonged the two associations at the same time. They had a consciousness of a common occupation group as a doctor who had learned Western medicine. Thus, they actively cooperated to keep their profits against Chinese medicine and enjoy their reputation. Their cooperation emitted light particularly in translation of medical terms and unified works. Thanks to cooperation, the two associations selected medical terminologies by properly using the cases of the West and Japan. Additionally, medical schools of the Britain - America faction and the Germany – Japan faction produced various levels of the Western Medicine Group doctors for China to timely respond to the rapidly increased demand. However, a conflict over the promotion of hygiene administration and the unification, organization of medical education did not end. This conflict was deepening as the Nanjing nationalist government promoted sanitary administration. It was the Britain - America faction who seized a chance of victory. It was because figures from the Britain - America faction held important positions in the hygiene department. Of course, some related to the National Medical and Pharmaceutical Association of China were also involved in the hygiene department; however, most took charge of simple technical tasks, not having a significant impact on hygiene administration. To solve the problem of factions of the Western Medicine Group, the Britain - America faction or the Germany - Japan faction had to arrange the education system with a strong power, or to organize a new association of two factions mixed, as in Chinese faction(zhonghuapai). But an effort of the Britain - America faction to unify the systems of medical schools did not reach the Germany - Japan faction’s medical schools. Additionally, from 1928, executives of the two Chinese medical associations discussed their merger; however they could not agree because of practitioners’interests involved. Substantially, a conflict between factions of the Western Medicine Group continued even until the mid-1930s. This implies that the then Chinese government had a lack of capacity of uniting and organizing the medical community. KCI Citation Count: 4